Reassemblable quasi-chip free-flow electrophoresis with simple heating dispersion for rapid micropreparation of trypsin in crude porcine pancreatin - Geng, Jia-Zhen; Shao, Jing; Yang, Jing-Hua; Pang, Bo; Cao, Cheng-Xi; Fan, Liu-Yin (Electrophoresis, 2011)
An increasing number of small biosamples (e.g. proteins and enzymes) need micropreparation in lab. However, neither large‐scale free‐flow electrophoresis (LS‐FFE) nor chip FFE (C‐FFE) could fit the growing demands. Herein, a simple quasi‐chip FFE (QC‐FFE) was constructed. In contrast to C‐FFE, the features of QC‐FFE are as follows: (i) its separation chamber is reassemblable and rewashable avoiding discard of C‐FFE due to blockage of solute precipitation in chamber; (ii) its chamber size is 45 mm×30 mm×(80–500) μm (108–654 μL volume) having function of micropreparation; (iii) there are up to 16 outlets in QC‐FFE bestowing fine fraction for micropurification. The QC‐FFE was used for the micropurification of model enzyme of self‐digestible trypsin in crude pancreatin. Under the given conditions, the purification factor of enzyme was 11.7, the specific activity reached 6236 U/mg, the run time for 19 μL sample purification was 45 s and the throughput of trypsin was 3.34 mg/h, and the yield of pure trypsin was 55.2%. All of the results show the feasibility of enzyme micropreparation via QC‐FFE. The developed device and procedure have potential use to other micropurification of protein or peptide sample.